2022
DOI: 10.1002/jcp.30849
|View full text |Cite
|
Sign up to set email alerts
|

PTH1R translocation to primary cilia in mechanically‐stimulated ostecytes prevents osteoclast formation via regulation of CXCL5 and IL‐6 secretion

Abstract: Osteocytes respond to mechanical forces controlling osteoblast and osteoclast function. Mechanical stimulation decreases osteocyte apoptosis and promotes bone formation. Primary cilia have been described as potential mechanosensors in bone cells. Certain osteogenic responses induced by fluid flow (FF) in vitro are decreased by primary cilia inhibition in MLO‐Y4 osteocytes. The parathyroid hormone (PTH) receptor type 1 (PTH1R) modulates osteoblast, osteoclast, and osteocyte effects upon activation by PTH or PTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
6
0
5
Order By: Relevance
“…Parathyroid hormone (PTH) receptor 1 (PTH1R) is a B-group G protein-coupled receptor (GPCR), which plays an important role in bone metabolism, and activation of PTH1R was found to regulate osteoclasts. Tirado-Cabrera ( 62 ) reported the localization of PTH1R to primary cilia, which confirmed that primary cilia in osteoblasts are necessary for proper communication with osteoclasts.IL-6 secretion is increased when PTH1R is silenced. Previous studies have shown that IL-6 enhances osteoblast-mediated osteoclastogenesis by promoting the activities of JAK2 and RANKL ( 63 ).…”
Section: The Role Of Primary Cilia In Bone Metabolismmentioning
confidence: 70%
“…Parathyroid hormone (PTH) receptor 1 (PTH1R) is a B-group G protein-coupled receptor (GPCR), which plays an important role in bone metabolism, and activation of PTH1R was found to regulate osteoclasts. Tirado-Cabrera ( 62 ) reported the localization of PTH1R to primary cilia, which confirmed that primary cilia in osteoblasts are necessary for proper communication with osteoclasts.IL-6 secretion is increased when PTH1R is silenced. Previous studies have shown that IL-6 enhances osteoblast-mediated osteoclastogenesis by promoting the activities of JAK2 and RANKL ( 63 ).…”
Section: The Role Of Primary Cilia In Bone Metabolismmentioning
confidence: 70%
“…157,158 Osteocytes with PTH1R translocation to primary cilia can prevent osteoclast formation under FSS by manipulating CXCL5 and IL-6 secretion. 159 Therefore, restoring or enhancing the function of primary cilia may be a potential strategy to combat bone loss associated with mechanical disuse, such as microgravity. Nevertheless, current studies do not support the existence of primary cilia in osteoclasts.…”
Section: Mechanosensitive Structuresmentioning
confidence: 99%
“…In addition, compressive stress can also stimulate angiogenesis, which is essential for osteoclast generation and represents a potential mechanism underlying the remodeling of periodontal bone (Wang, Zheng, et al, 2022). However, The parathyroid hormone receptor type 1 is translocated to primary cilia in mechanically stimulated bone cells, preventing the formation of osteoclasts by regulating the secretion of CXCL5 and IL‐6, suggesting that mechanical stress also inhibits osteoclast recruitment and differentiation (Tirado‐Cabrera et al, 2022).…”
Section: Mechanical Stress Affects Cell Death In Pdlcsmentioning
confidence: 99%